Neuroadaptation and quality of vision - Spyra, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The aim of this article is to introduce and elaborate upon neuroadaptation and quality of vision in the available literature. Material and methods: The information contents in the article comes from several studies in literature performed on groups of patients with different forms of aberrations and neuroadaptation problems. Visual quality and satisfaction in the most of tchem were very poor. Results: After surgical treatment – corneal or intraocular, most of patients were highly satisfied. Photorefractive keratectomy and/ or lens surgery using diffractive multifocal lenses gave decrease optical ocular aberrations and improve quality of vision and life. Conclusions: Based on current literature decrease of ocular aberrations gives better neuroadaptation and in consequence improves quality of vision and life. To establish these data, further studies on representative group of patients are necessary.